RETRACTED: Thermodynamic condition of cylinder diesel group for infrastructure objects under high temperatures - Absalyamov D.R.; Litvinova N.B.; Tupitsin Y.E.; Shishkin E.V. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001